Maximal aerobic capacity versus vital capacity which Cassel relationships determine the cardiorespiratory fitness among soccer players - Mohammed Zerf (Turkish Journal of Kinesiology, 2017)
Our study evaluated relationships between two surrogates measured vital capacity and aerobic capacity to predict the Cardiorespiratory Fitness among Soccer Players. Based on the background, which confirms that the vital capacity is a limiting factor of aerobic capacity.  For this proposed, a total of 163 male soccer players under 17 years from Algerian football championship participated in the present study. There VO2max were estimated based on the formula Cooper Test (VO2max = 22.351 d (km) - 11.288 (ml/min/kg)). As well as their vital capacity was calculating based on formula [vital capacity (ml) = (27.63 - 0.112 × age) × height (cm)]. Based on the statistical applied. Our results confirm: 1) There was a significant relation between soccer players' maximal aerobic Capacity and vital capacity. 2) Soccer players' maximal aerobic Capacity and vital capacity; are the features affecting each other.